2012
DOI: 10.5530/ijmedph.2.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factor Analysis of Acute Respiratory tract Infections in Rural areas of Kashmir valley under 5 Years of Age

Abstract: Research Question: How important is acute respiratory tract infections in children less than 5 years of age and what are the main factors that need attention. Objective: To determine the magnitude of ARI under 5 years of age in rural areas of Kashmir valley. 2) To identify various risk factors responsible for ARI. Methodology: Community based Cross sectional study using multistage sampling procedure was used to study 1644 children. A house to house survey was carried out in the defined geographical region in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
1
10
1
1
Order By: Relevance
“…Generally, education helps to improve the knowledge of maternal caretaking with respect to the risk factors responsible for ARIs, but this study revealed no difference in the prevalence of ARIs in the children born to mothers with varied educational levels. This was in contrast to the results of many studies ( 1 , 10 , 17 , 19 ), which have shown a higher prevalence of ARIs in the children born to mothers with primary education levels compared to those born to highly educated mothers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Generally, education helps to improve the knowledge of maternal caretaking with respect to the risk factors responsible for ARIs, but this study revealed no difference in the prevalence of ARIs in the children born to mothers with varied educational levels. This was in contrast to the results of many studies ( 1 , 10 , 17 , 19 ), which have shown a higher prevalence of ARIs in the children born to mothers with primary education levels compared to those born to highly educated mothers.…”
Section: Discussioncontrasting
confidence: 99%
“…ARI is the third most common individual cause of death in both developed and developing countries ( 1 ). The prevalence of ARI reported by the various studies ranges from 20 to 30% ( 7 , 19 , 20 ). This study found the prevalence of ARI to be 50.4% among under-five children which is similar to the other studies ( 6 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute malnutrition was significantly associated with childhood ARI in this study. Studies from India have previously highlighted nutritional status as being a significant risk factor for childhood ARI, with 2.4-to 7.1-fold increased odds of ARI in those who are malnourished (Goel et al, 2012;Mir et al, 2012;Arun et al, 2014;Naik et al, 2016). This may be because malnutrition predisposes to an immunodeficient state, which increases the risk of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…On average, under-five children suffer about four to five episodes of ARI per year. ARI is responsible for approximately 30-50% of visits to health facilities and accounts for 20-40% of under-five hospital admissions (Mir et al, 2012). From an estimated 10.4 million deaths among under-five children worldwide, 73% were attributable to ARIs (Anjum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%